Histone H2B Ubiquitination Promotes the Function of the Anaphase-Promoting Complex/Cyclosome in Schizosaccharomyces pombe - Elmore, Zachary C. (Genetics Society of America, 2014)
Ubiquitination and deubiquitination of proteins are reciprocal events involved in many cellular processes, including the cell cycle. During mitosis, the metaphase to anaphase transition is regulated by the ubiquitin ligase activity of the anaphase-promoting complex/cyclosome (APC/C). Although the E3 ubiquitin ligase function of the APC/C has been well characterized, it is not clear whether deubiquitinating enzymes (DUBs) play a role in reversing APC/C substrate ubiquitination. Here we performed a genetic screen to determine what DUB, if any, antagonizes the function of the APC/C in the fission yeast Schizosaccharomyces pombe. We found that deletion of ubp8, encoding the Spt-Ada-Gcn5-Acetyl transferase (SAGA) complex associated DUB, suppressed temperature-sensitive phenotypes of APC/C mutants cut9-665, lid1-6, cut4-533, and slp1-362. Our analysis revealed that Ubp8 antagonizes APC/C function in a mechanism independent of the spindle assembly checkpoint and proteasome activity. Notably, suppression of APC/C mutants was linked to loss of Ubp8 catalytic activity and required histone H2B ubiquitination. On the basis of these data, we conclude that Ubp8 antagonizes APC/C function indirectly by modulating H2B ubiquitination status.